2016
DOI: 10.4314/bajopas.v9i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rotavirus infection in children with gastroenteritis attending three selected hospitals in Kano metropolis, Nigeria

Abstract: The study aimed at detecting the incidence of rotavirus infection among children with gastroenteritis in Kano Metropolis. It was a descriptive cross-sectional study and a total of 200 stool samples were randomly collected and assayed for the presence of rotavirus antigens using Enzyme Linked Immunosorbent Assay and confirmed using Real Time Polymerase Chain Reaction. The study revealed that 21/200 (10.5%) stool samples were positive for rotavirus antigen and more males 13/21(6.5%) were positive than females 8/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…[ 25 ] There is a higher detection of Rotavirus among males (28.1%) than in females (11.2%) in this study. This is similar to report from Nigeria[ 26 ] in 2016 with a higher prevalence among males than females. The high prevalence in a male could be due to male children preferring playing with their mates outside than females who are mostly indoor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[ 25 ] There is a higher detection of Rotavirus among males (28.1%) than in females (11.2%) in this study. This is similar to report from Nigeria[ 26 ] in 2016 with a higher prevalence among males than females. The high prevalence in a male could be due to male children preferring playing with their mates outside than females who are mostly indoor.…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence in a male could be due to male children preferring playing with their mates outside than females who are mostly indoor. [ 26 ] The report observed in this study revealed the highest prevalence of 30.3% in ages 6–10 years. This is similar to results in Iraq,[ 7 ] where the prevalence of Rotavirus was highest in children under the age of 18 years among asymptomatic Rotavirus infection.…”
Section: Discussionmentioning
confidence: 49%